Studi komparasi model pembelajaran scramble dan concept sentence terhadap keterampilan menulis rangkuman ditinjau dari motivasi menulis - Frisiliani Ayu Widorusmi; Slamet St. Y; Joko Daryanto (Universitas Sebelas Maret, 2020)
The purpose of this study was to determine the Comparative Study of Scramble Learning Model and Concept Sentence on Summary Writing Skills in terms of Learning Motivation. (Experimental Research on Class V Semester 2 SD Students in Laweyan District, 2019/2020 Academic Year). The population of this study was all students in grade V SD Negeri in Laweyan District, Surakarta City for the 2019/2020 school year, totaling 38 schools. The sample in this study was grade V of some public elementary schools in Laweyan District, Surakarta City. Theexperimental class in this study was in class V SD Negeri Bumi 1 and SD Negeri Bratan III, while the control class was in class V SD Negeri Pajang III and SD Negeri Tegalsari. Data collection techniques in this study used a test (post-test) and non-test (questionnaire). The data analysis technique used in this study was the Two Way Variance Analysis (Two Way Anava) with a significant level of α = 0.05. The results showed that there were differences in summary writingskills between students who were taught by the Scramble learning model and students who were taught with the Concept Sentence learning model, indicated by the acquisition of the Sig. = 0.000 <0.05. There are differences in summary writing skills between students who have high learning motivation and students who have low learning motivation. This is indicated by the acquisition of the Sig. = 0.000 <0.05. There is an interaction between the learning model and learning motivation on summary writing skills indicated by the acquisition of Sig. = 0.000 <0.05.